The Influence of Work-Life Balance and Emotional Intelligence on Organizational Citizenship Behavior (OCB) Among Security Personnel at PT. Gitra Sandi Borlak - Olivia Tiara; Francisco S. P. Silalahi; Osly Usman; G. Borlak (Green Publisher Indonesia, 2026)
This study investigates the influence of Work-Life Balance (WLB) and Emotional Intelligence (EI) on Organizational Citizenship Behavior (OCB) among security personnel at PT. Gitra Sandi Borlak. Human resource performance, particularly discretionary behaviors beyond formal duties, is critical for service quality and client satisfaction in security services. Observations indicated variations in OCB, suggesting that differences in WLB and EI may explain these disparities. The study aims to examine the individual and combined effects of WLB and EI on OCB. A quantitative research design using a saturated sampling approach was employed, involving 62 security personnel. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression, with classical assumption tests conducted to ensure the validity and reliability of the analytical model. The results indicate that both WLB (B = 0.418, t = 4.107, p < 0.05) and EI (B = 0.372, t = 3.685, p < 0.05) have positive and significant effects on OCB, both individually and simultaneously (F = 28.914, p < 0.05), explaining 49.5% of the variance. These findings highlight the importance of maintaining a balance between work and personal life and enhancing emotional competencies to foster discretionary behaviors. The study concludes that organizations can improve OCB through balanced work scheduling and targeted EI development programs, while future research could explore mediating variables and comparisons across multiple organizations.